2011
DOI: 10.2166/wst.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

Enteric viruses in New Zealand drinking-water sources

Abstract: This study determined whether human pathogenic viruses are present in two New Zealand surface waters that are used as drinking-water sources. Enteric viruses were concentrated using hollow-fibre ultrafiltration and detected using PCR for adenovirus (AdV), and reverse transcription PCR for norovirus (NOV) genogroups I-III, enterovirus, rotavirus (RoV) and hepatitis E virus (HEV). Target viruses were detected in 106/109 (97%) samples, with 67/109 (61%) samples positive for three or more viral types at any one ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Different filtration methods, most of them applying multiple filtration steps, have been described. This includes combinations of hollow fibre ultrafiltration (Williamson et al, 2011;Marcheggiani et al, 2015), other ultrafiltration devices (Kitajima et al, 2009;Rutjes et al, 2009;Verma and Arankalle, 2010;Givens et al, 2016) and/or positively (Rutjes et al, 2009;Steyer et al, 2011;Li et al, 2014b) or negatively (Kitajima et al, 2009) charged filter membranes. Glass wool filtrations (Kokkinos et al, 2012;Givens et al, 2016) and flocculation at low pH (Kokkinos et al, 2012) have also been described.…”
Section: Methods For Virus and Rna Extraction From Food And Watermentioning
confidence: 99%
“…Different filtration methods, most of them applying multiple filtration steps, have been described. This includes combinations of hollow fibre ultrafiltration (Williamson et al, 2011;Marcheggiani et al, 2015), other ultrafiltration devices (Kitajima et al, 2009;Rutjes et al, 2009;Verma and Arankalle, 2010;Givens et al, 2016) and/or positively (Rutjes et al, 2009;Steyer et al, 2011;Li et al, 2014b) or negatively (Kitajima et al, 2009) charged filter membranes. Glass wool filtrations (Kokkinos et al, 2012;Givens et al, 2016) and flocculation at low pH (Kokkinos et al, 2012) have also been described.…”
Section: Methods For Virus and Rna Extraction From Food And Watermentioning
confidence: 99%
“…Norovirus belonging to GI are significantly more likely to have been transmitted via water than by other routes of transmission, and are therefore thought to be more stable in water than GII strains. Noroviruses have been detected in a wide range of water environments such as sewages, municipal water, rivers, recreational waters, and groundwater throughout the world [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Viral Pathogens Transmitted Through Water Norovirusmentioning
confidence: 99%
“…The occurrence of enteroviruses in coastal waters in both bathing and non-bathing sites is documented worldwide [45][46][47][48][49][50]. Enteroviruses have also been found in rivers [49,[51][52][53][54][55], lakes [56,57], groundwater [29, [58][59][60][61] and in both untreated and finished drinking water supplies [30,38,55,62,63]. Despite the widespread presence of these viruses, however, few drinking water-related outbreaks have been reported [64][65][66][67], only two outbreaks of recreational waterborne coxsackievirus, nine echovirus outbreaks concentrated between 1990 and 2005 [11] and sporadic echovirus 30 outbreaks in swimming pool.…”
Section: Enterovirusmentioning
confidence: 99%
“…Both tools have demonstrated that many virus types are present in environmental and drinking waters throughout the world [1][2][3][4][5][6] . Their use coupled with sequencing of amplified genomic fragments during disease outbreak investigations has provided evidence for waterborne virus transmission, as they have shown that the virus found in the drinking water is identical to that shed by outbreak patients [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%